SOME MOISTURE DEPENDENT THERMAL PROPERTIES AND BULK DENSITY OF Prosopis Africana SEEDS (OKPEYE) (Nigerian Journal of Technology, 2017)
The thermal heat conductivity, specific heat capacity, thermal heat diffusivity and bulk density of Prosopis africana seeds were determined as a function of moisture content. Specific heat capacity was measured by the method of mixture while the thermal heat conductivity was measured by the guarded hot plate method. Thermal heat diffusivity was calculated from the experimental results obtained from specific heat capacity, thermal heat conductivity and bulk density. The bulk density for Prosopis africana (PA) seeds decreased from 890kg m-3 to 590kg m-3 as moisture content increased from 4 to 20% wet basis (w.b). Specific heat capacity increased from 2760J kg-1 ºC-1 to 2960J kg-1 ºC-1with increasing moisture content. The thermal heat conductivity ranged between 0.70 and 0.90W m-1oC-1 when moisture content rose from 4% to 20% (w.b). Thermal heat diffusivity increased from 2.7 10-7 to 4.2 10-7m2 s-1 as moisture content increased from 4 to 20% (w.b). The values obtained for these thermal properties and bulk density could be useful for design of systems for heat treatment of Prosopis africana seeds.  http://dx.doi.org/10.4314/njt.v36i3.38